Civic education at crossroads : the christian nationalist threat to public schools - Henry, Bryan J. (New York, NY : Routledge, 2024)
"This book turns to political theory as a framework for understanding the rise of political and religious extremism, and in particular the Christian Nationalist position, identifying solutions to civic challenges, and arguing for the vital role that public schools play in providing the civic education that prepares young people for participation in democratic self-government. Drawing on scholarly debates between liberal and republican political theorists, the author maintains that if we want to preserve our republic, then policymakers and educators must unapologetically promote a normative "vision of good citizenship" that cultivates in students the requisite civic virtue and rational autonomy needed to defend democracy from the rise of illiberal extremism. A timely contribution to academic debates about the role of civic education in the preservation of democracy, it will appeal to scholars, educators and policymakers concerned with the future of civic education, as well as the philosophy of education, political science, and educational policy"--
Keywords: Civics -- Study and teaching -- United States; Nationalism -- Religious aspects -- Christianity; Citizenship -- Religious aspects -- Christianity; Political science -- United States -- Philosophy; Religion in the public schools -- United States; EDUCATION / General; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / Civics & Citizenship